Peningkatan Kemampuan Siswa Membaca Permulaan Melalui Metode Struktural Analitik Sintetik (SAS) di Kelas I SD Negeri 012 Koto Kari - Mahrani, Mahrani (Institut Teknologi Pendidikan Indonesia, 2023)
This research is motivated by the influence of the covid 19 pandemic which has created an onlinelearning system that has a significant impact on early reading learning. Beginning reading, whichis the essence of basic education, which determines success in further formal education, must face difficulties due to limited instructors and the educational infrastructure itself. Even though the success of the whole process of learning activities itself is largely determined by the mastery of reading skills starting from initial reading to reading comprehension. Based on this, research was carried out to improve initial reading ability using the synthetic structural analytic method (SAS) to see and describe the effectiveness and understanding of each stage. This research was conducted in Class I SD Negeri 012 Koto Kari using Classroom Action Research (CAR). The results that were concluded from this study stated that the synthetic structural analytic method (SAS) was a method that was quite effective and had a significant impact on improving the ability of students to read beginning in class I SD Negeri 012 Koto Kari. Besides that, teacher activity and creativity are needed to increase student activity. Furthermore, these two activities will affect student learning outcomes. The success of learning is determined by the teacher's ability to manage the classroom, including the use of various relevant teaching methods and local conditions and student characteristics.